The Creation of Keris with Honeybee Pattern Penciptaan Keris Dhapur Lebah Madu: - - Putranto , Eko; Darmojo, Kuntadi Wasi (TEXTURE Art and Culture Journal, 2025)
The creation of this final project focuses on the theme of the Honeybee (Apis mellifera) as the inspiration for contemporary keris creation, specifically the keris dhapur Lebah Madu. This project aims to produce keris that reflect the characteristics, values, and philosophical aspects of the Honeybee. The Honeybee is an intriguing subject for a final project, visualized through gold-engraved motifs on the keris blade. The method for this final project involves a three-stage, six-step creation process, consisting of exploration, planning, and realization stages. The exploration stage includes observation, literature review, and interviews. The planning stage involves creating alternative sketches and working drawings. The realization stage includes the preparation of tools and materials, blade making, warangka (sheath) making, hilt making, mendak (hilt ring) making, pendok (sheath cover) making, and antup (decorative cover) making. This final project results in the creation of three keris titled: keris dhapur Madukara, keris dhapur Bhirawa, and keris dhapur Tala Kencana. The selection of the Honeybee's characteristics as the motif idea, using the tinatah technique applied to the keris ricikan (details), is expected to add aesthetic value to each dhapur (design) of the keris.